2013
DOI: 10.1002/0471141755.ph1425s61
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cancer Stem Cells (CSCs) and Mechanisms of Their Regulation: Implications for Cancer Therapy

Abstract: The identification of small subpopulations of cancer stem cells (CSCs) from blood mononuclear cells in human acute myeloid leukemia (AML) in 1997 was the landmark observation for recognizing the potential role of CSCs in tumor aggressiveness. Two critical properties contribute to the functional role of CSCs in the establishment and recurrence of cancerous tumors: their self-renewal capacity and their potential to differentiate into unlimited heterogeneous populations of cancer cells. These findings suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
187
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(210 citation statements)
references
References 118 publications
(218 reference statements)
4
187
0
3
Order By: Relevance
“…Pancreatic CSC populations account for less than 1% of all pancreatic cancer cells [14] . The pancreatic CSCs identified so far are CD133, CD24, CD44, EPCAM, ESA, c-Met, Aldh1, and more recently DclK1 and Lgr5 [9][10][11][12][13][14][15][16][17][18] . These pancreatic CSC markers are well known based on several xenograft studies.…”
Section: Role Of Csc In Pcmentioning
confidence: 99%
See 2 more Smart Citations
“…Pancreatic CSC populations account for less than 1% of all pancreatic cancer cells [14] . The pancreatic CSCs identified so far are CD133, CD24, CD44, EPCAM, ESA, c-Met, Aldh1, and more recently DclK1 and Lgr5 [9][10][11][12][13][14][15][16][17][18] . These pancreatic CSC markers are well known based on several xenograft studies.…”
Section: Role Of Csc In Pcmentioning
confidence: 99%
“…All these markers may mark themselves or co-express to show the CSC properties [19][20][21] . CD133 pancreatic CSC cells co-express the CXCR4 receptor at the invading margins of human pancreatic ductal tumors [14,19] . Other CSC markers that co-express (CD24 + /CD44 + /EPCAM and CD133 + ) show CSC properties making them often resistant to chemo and radiotherapy.…”
Section: Role Of Csc In Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that tumors originate from cancer stem cells (4). However, the continuous differentiation of stem cells during the process of tumor growth results in daughter cells with variations in their genetic and molecular characteristics following several rounds of proliferation, leading to differences in tumor growth, invasiveness, drug susceptibility and prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, there is a very small population of stem cells and cancer stem cells (CSCs) in normal and cancerous tissues, respectively [2]. Hence, IHC has several advantages over IF technique including: 1) capability of being repeatedly used in order to search for few positive cells, 2) no reduction in signal intensity, 3) provides superior morphological information, and 4) could be utilized to distinguish between normal and cancerous tissue.…”
Section: Introductionmentioning
confidence: 99%